ANALISIS OVERALL CASH FLOW RATIO PADA PT. PELABUHAN INDONESIA IV (PERSERO) CABANG PAREPARE - Hasdiana, Hasdiana (Universitas Muhammadiyah Parepare, 2021)
The purpose of the research conducted by researchers is to find out how much revenue and expenses are and to analyze to find out the amount of Overall Cash Flow Ratio at PT Pelabuhan Indonesia IV (PERSERO) Parepare branch. This research method is descriptive, this research is quantitative which tries to answer a large amount of revenue and expenditure at PT Pelabuhan Indonesia IV (PERSERO) Parepare branch. The results of this study state that how to manage cash from the income received by the company, expenditures, namely expenses made by the company in meeting all needs at PT Pelabuhan Indonesia IV (PERSERO) Parepare branch, and Overall Cash Flow Ratio which overall shows how well the company generates cash. and provide relevant information about cash receipts and disbursements in a given period. The data analysis used by the author is accounting analysis to find Cash Flow and Overall Cash Flow Ratio analysis.